2009
DOI: 10.1111/j.1528-1167.2009.02175.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemiconvulsion–hemiplegia syndrome in a patient with severe myoclonic epilepsy in infancy

Abstract: Summary We report a 2‐year‐old girl who had repeated febrile or afebrile seizures since infancy. Prolonged left/right hemiconvulsions and myoclonus of the eyelids/extremities with generalization to tonic–clonic seizures, were refractory to antiepileptic agents. At age 1 year and 4 months, she contracted rotavirus infection, and developed status epilepticus with persistent right hemiclonic seizures. Left unilateral brain edema with subsequent emergence of cortical laminar necrosis and white matter lesions, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 9 publications
1
31
0
2
Order By: Relevance
“…It is of note that even on quantitative analysis, there was no neuropathological evidence of neuronal loss in the post-mortem adult cases with Dravet syndrome, showing that Dravet syndrome per se , and SCN1A mutation (one post-mortem adult case with Dravet syndrome), are not sufficient to cause hippocampal neuronal loss despite decades of drug-resistant seizures and recurrent episodes of status epilepticus. Rarely, significant clinical and imaging changes have been reported in Dravet syndrome following status epilepticus (Sakakibara et al ., 2009; Chipaux et al ., 2010; Tang et al ., 2011). There may be age-dependent vulnerability of the brain to injury induced by seizures (Haut et al ., 2004), but it is difficult to separate out effects of seizures on the brain from the effects of the disease process per se , and the effects of drugs and other factors.…”
Section: Discussionmentioning
confidence: 99%
“…It is of note that even on quantitative analysis, there was no neuropathological evidence of neuronal loss in the post-mortem adult cases with Dravet syndrome, showing that Dravet syndrome per se , and SCN1A mutation (one post-mortem adult case with Dravet syndrome), are not sufficient to cause hippocampal neuronal loss despite decades of drug-resistant seizures and recurrent episodes of status epilepticus. Rarely, significant clinical and imaging changes have been reported in Dravet syndrome following status epilepticus (Sakakibara et al ., 2009; Chipaux et al ., 2010; Tang et al ., 2011). There may be age-dependent vulnerability of the brain to injury induced by seizures (Haut et al ., 2004), but it is difficult to separate out effects of seizures on the brain from the effects of the disease process per se , and the effects of drugs and other factors.…”
Section: Discussionmentioning
confidence: 99%
“…They mentioned 2 children with residual severe neurological defi cits after prolonged status epilepticus triggered by acute febrile illness [7] . Only one case of hemiconvulsion-hemiplegia syndrome has been reported in a child who subsequently developed a characteristic feature of Dravet syndrome [8] . Chipaux et al reported an unusual pattern in 3 patients with Dravet syndrome who had refractory status epilepticus followed by severe cognitive and motor deterioration, and whose neuroimages showed anoxic-ischemic like lesions [1] .…”
Section: Discussion ▼mentioning
confidence: 99%
“…However, repeated febrile and afebrile seizures since infancy have been reported 1. Seizures may be simple partial, partial with secondary generalisation or status epilepticus in nature 4.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral hemiatrophy is a consistent finding in all patients by cranial CT and/or MRI 2–6. Furthermore, vasospasms of cerebral vascular smooth muscle has been proposed as the mechanism of seizure by Yamazaki et al 2 Potential risk of HHE with severe myoclonic epilepsy in infancy has been proposed by Sakakibara et al 1…”
Section: Discussionmentioning
confidence: 99%